2013
DOI: 10.15728/bbr.2013.10.3.5
|View full text |Cite
|
Sign up to set email alerts
|

The innovation process in the organizational context: an analysis of helping and hindering factors

Abstract: This article investigates the phenomenon of innovation in the organizational context, considering its multifaceted and multidimensional nature, with the objective of identifying factors that facilitate or hinder the process of implementing new ideas and practices. We performed an exploratory qualitative case study of three Brazilian organizations. The results obtained by means of semi-structured interviews enabled categorization of the innovation processes in the organizations studied. We identified ten factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 22 publications
(55 reference statements)
0
11
0
Order By: Relevance
“…In essence, the TMT should be prepared to take up the ownership of the adoption decision for the SCM to be successful (Cooper et al , 1997; Burgess et al , 2006; Sandberg and Abrahamsson, 2010; Kotzab et al , 2011). Lack of top management support has been identified as a barrier to organizational innovation (Souza and Bruno-Faria, 2013). Management style has been identified as a barrier to SCM adoption (Saad and Patel, 2006).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In essence, the TMT should be prepared to take up the ownership of the adoption decision for the SCM to be successful (Cooper et al , 1997; Burgess et al , 2006; Sandberg and Abrahamsson, 2010; Kotzab et al , 2011). Lack of top management support has been identified as a barrier to organizational innovation (Souza and Bruno-Faria, 2013). Management style has been identified as a barrier to SCM adoption (Saad and Patel, 2006).…”
Section: Methodsmentioning
confidence: 99%
“…The presence of slack resources helps an organization to undertake initiatives and programs (Rogers, 1983; Damanpour, 1992; Crossan and Apaydin, 2010; Hueske and Guenther, 2015) such as SCM adoption. Lack of resources has been identified as a barrier to organizational innovation (Souza and Bruno-Faria, 2013; Sandberg and Aarikka-Stenroos, 2014). Lack of resources (Fawcett et al , 2008) and lack of SCM expertise (Manzouri et al , 2010) have been identified as barriers to SCM.…”
Section: Methodsmentioning
confidence: 99%
“…Innovation is the knowledge practice that converts knowledge into new products and services [7]. Innovation has been also characterised as a practice that encompasses organisational learning, with a certain degree of ambiguity and intrinsic probability for transformation, based on people's expertise, technological advancements, and organisational cultural elements, thus necessitating the elucidation of problems during its enactment [8]. Innovation is sometimes described as the improvement and application of novel ideas by experts who engage in transactions over time with others in the organisation [9].…”
Section: Innovationmentioning
confidence: 99%
“…These were: 1) firm-level challenges (lack of awareness of benefits; lack of internal IT expertise; lack of business process expertise; lack of budget; lack of affordable solutions; lack of qualified service providers; and lack of local language software); 2) ICT provider challenges (high cost of sales; high piracy rate; diverse needs of MSME; inability to scale); and 3) policy and infrastructure challenges (poor internet connectivity; unreliable power supply; financing; lack of policy clarity on innovations; data security issues), (NMCC and NASSCOM, 2010). Souza and Bruno-Faria (2013), investigated barriers to organizational innovations in Brazil based on case studies of three organizations. They found twelve barriers.…”
Section: Other Barrier Frameworkmentioning
confidence: 99%
“…The summary of the conceptual factors from literature and expert interviews are listed in Error! Reference source not found.. Rogers, 1962Rogers, , 2003Williamson, 1975;Tornatzky and Klein, 1982;Ramamurthy, 1990;Barney, 1991;Frambach et al, 1998;Ketchen and Giunipero, 2004;OECD, 2005;Leichter, 2006;Williamson, 2008;Fawcett et al, 2008;NMCC and NASSCOM, 2010 Rogers, 1962Rogers, , 2003Barney, 1991;OECD, 2005;Fawcett et al, 2008;NMCC and NASSCOM, 2010;Souza and Bruno-Faria, 2013 Rogers, 1962Rogers, , 2003Tornatzky and Fleischer, 1990;Frambach et al, 1998 Based on a comprehensive analysis of the factors collated from theoretical bases, and those identified from indepth expert interviews, a new theoretical framework for the study of barriers to SCM adoption in India has been proposed in this study (Error! Reference source not found.).…”
Section: Synthesis Of the Theoretical Modelmentioning
confidence: 99%